Alternative oxidase pathway is involved in the exogenous SNP-elevated tolerance of Medicago truncatula to salt stress - Jian, Wei; Zhang, Da-wei; Zhu, Feng; Wang, Shuo-xun; Pu, Xiao-jun; Deng, Xing-Guang; Luo, Shi-Shuai; Lin, Hong-hui (Journal of plant physiology, 2016)
Exogenous application of sodium nitroprusside (SNP) would enhance the tolerance of plants to stress conditions. Some evidences suggested that nitric oxide (NO) could induce the expression of alternative oxidase (AOX). In this study, Medicago truncatula (Medicago) was chosen to study the role of AOX in the SNP-elevated resistance to salt stress. Our results showed that the expression of AOX genes (especially AOX1 and AOX2b1) and cyanide-resistant respiration rate (Valt) could be significantly induced by salt stress. Exogenous application of SNP could further enhance the expression of AOX genes and Valt. Exogenous application of SNP could alleviate the oxidative damage and photosynthetic damage caused by salt stress. However, the stress resistance was significantly decreased in the plants which were pretreated with n-propyl gallate (nPG). More importantly, the damage in nPG-pretreated plants could not be alleviated by application of SNP. Further study showed that effects of nPG on the activities of antioxidant enzymes were minor. These results showed that AOX pathway played an important role in the SNP-elevated resistance of Medicago to salt stress. AOX could contribute to regulating the accumulation of reactive oxygen (ROS) and protect of photosystem, and we proposed that all these were depend on the ability of maintaining the homeostasis of redox state.